(untitled) - Dossey, Larry (San Francisco, 1999)
Larry Dossey forever changed our understanding of the healing process with his phenomenal New York Times bestseller, Healing Words. Now the man considered on of the pioneers of mind/body medicine provides the scientific and medical proof that the spiritual dimension works in therapeutic treatment, exploding the boundaries of the healing arts with his most powerful book yet.
Keywords: Medicine and psychology,Y học và tâm lý học